A Single-Center Experience with Dynamic Compression Bracing for Children with Pectus Carinatum - Poola, Ashwini Suresh; Pierce, Amy L.; Orrick, Beth A.; Peter, Shawn David St.; Snyder, Charles L.; Juang, David; Aguayo, Pablo; Fraser, Jason D.; Holcomb, George W., III (European Journal of Pediatric Surgery, 2018)
Objective Bracing for pectus carinatum (PC) has emerged as an alternative to surgical correction. However, predictive factors for bracing remain poorly understood, as much of the data have been reported from small series.Materials and Methods We reviewed a prospective dataset in patients with PC who underwent dynamic compression bracing (DCB) from July 2011 to July 2016. Bracing was initiated in patients > 10 years of age with a significant PC and desire for bracing. Data were analyzed for those observed two or more times after the brace was fitted to the patient.Results A total of 503 patients were evaluated for PC and 340 (68%) underwent DCB. Eighty-five percent were males with an average age of 14 ± 2 years. There was a positive correlation of age with pressure of initial correction (PIC, r = 0.2). One patient underwent operative correction as the initial therapy. Two hundred seventeen patients had two or more visits after the patient was fitted for the brace. The mean PIC in this cohort was 4 psi (range: 1.5–7.8), and the median duration of bracing in this group was 16 months (IQR: 7–23 months). One hundred three patients (47%) achieved complete correction after an average bracing time of 7.5 months and were then placed in the retainer mode. Thirty patients successfully completed bracing therapy and required an average of 23 months of therapy (2 months–4 years). No patient recurred after bracing was completed, but one failed bracing and required operative correction. Complications included mechanical problems (8%), skin complications (10%), complaints of tightness (3%), and pain (2%).Conclusion DCB has both early and lasting effects in the correction of PC with minimal complications. Predictive factors for successful resolution of the PC include increased duration of DCB and lower initial PIC.
Keywords: pectus carinatum; dynamic compression bracing; chest wall deformities